Net water uptake within the ischemic penumbra predicts the presence of the midline shift in patients with acute ischemic stroke - Chen, Cuiping; Yang, Jianhong; Han, Qing; Wu, Yuefei; Li, Jichuan; Xu, Tianqi; Sun, Jie; Gao, Xiang; Huang, Yi; Parsons, Mark W.; Lin, Longting (Frontiers in Neurology, 2023)
Abstract Objective: To explore the association between net water uptake within the ischemic penumbra and midline shift in acute ischemic stroke patients. Methods: This was a retrospective cohort study on patients with anterior circulation stroke. Net water uptake within the acute ischemic core and penumbra was calculated based on admission multimodal CT. The primary outcome was severe cerebral edema measured by midline shift on 24-48-hour follow-up CT. Presence of significant midline shift was defined by a deviation of the septum pellucidum from the midline on follow-up CT at least 3 mm or greater due to mass effect by ischemic edema. The net water uptake was compared between patients with and without midline shift. This was followed by logistic regression analyses and receiver operating characteristic (ROC) to assess the predictive power of net water uptake in midline shift. Results: 133 patients were analyzed, 50 patients (37.6%) with midline shift and 83 patients (62.4%) without. Compared to patients without midline shift, patients with midline shift had higher net water uptake within core [6.8(3.2-10.4) vs. 4.9(2.2-8.1), P = 0.048] and higher net water uptake within ischemic penumbra [2.9 (1.8-4.3) vs. 0.2(-2.5–2.7), P＜0.001]. Penumbral net water uptake had higher predictive performance than net water uptake of core in midline shift [area under the curve: 0.708 vs. 0.603, p＜0.001]. Moreover, the penumbral net water uptake predicted midline shift in the multivariate regression model, adjusting for age, sex, admission National Institutes of Health Stroke Scale (NIHSS), diabetes mellitus, atrial fibrillation, ischemic core volume, and poor collaterals vessels status (OR=1.165; 95% CI=1.002–1.356; P=0.047). No significant prediction was found for the net water uptake of core in the multivariate regression model. Conclusion: Net water uptake measured acutely within the ischemic penumbra could potentially predict severe cerebral edema at 24-48 hours. Keywords: stroke; anterior circulation infarction; brain edema; midline-shift; net water uptake